Pengembangan LKPD Berbasis Whole Language Pada Pembelajaran Bahasa Indonesia Untuk Meningkatkan Kemampuan Membaca Siswa Kelas 2 Di SD Al Alawi Langkat - Nazuwa Laili; Intan Andriana Saputri (Institut Nalanda, 2024)
In learning activities, learning objectives can be achieved if students are active in learning activities. The form of student activity in learning can be seen from how they express their opinions, responsibilities and involvement in the study group. Therefore, teaching materials are needed that can make students active, as a tool to help in the learning process and can be used as a learning resource. One of them is the Student Worksheet (LKPD). However, the LKPD circulating in schools places more emphasis on questions and filling in questions without explaining how the process of obtaining answers to these questions. Therefore, it is necessary to develop LKPD which aims to determine the stages in making LKPD based on the whole language method in Indonesian language learning to improve the reading ability of grade 2 elementary school (SD) students, to determine the suitability of LKPD to be used as teaching materials, and to determine the response students towards LKPD based on the whole language method. This research was conducted at SD Al Alawi Langkat with the research subjects being 2nd grade elementary school students. LKPD is designed with appropriate whole language methodology and various activities that help understand concepts and differentiate learning in mind. The LKPD was then used in class 2 learning at SD Al Alawi Langkat. Data collection was carried out through observation, interviews and evaluation results during learning. The collected data was analyzed using qualitative descriptions. Research findings show that the use of LKPD in beginning reading learning can increase student engagement, conceptual understanding, and beginning reading skills. The use of LKPD increases students' interest and desire to learn. In addition, the series of activities in LKPD encourage independent learning and differentiation of learning according to the needs of each individual. Based on these data, it can be concluded that the development of LKPD as a learning medium for beginning reading was well received by teachers and students and has the potential to improve the beginning reading skills of grade 2 students at SD Al Alawi Langkat. The need to pay attention to the design and creation of appropriate worksheet to enable effective beginning reading learning in grade 2 of elementary school is an implication of this research.